AI-Driven Cybersecurity Architectures for National-Scale Digital Infrastructure - Araujo, Marcelo (Revista ft, 2026)
The increasing dependence of governments, financial institutions, and public services on interconnected digital infrastructures has significantly expanded the importance of cybersecurity strategies capable of protecting national-scale systems. Traditional cybersecurity architectures based on rule-based monitoring and signature-based detection have demonstrated limited effectiveness in environments characterized by high data volume, complex network interactions, and evolving cyber threats. Artificial intelligence and machine learning have emerged as fundamental technologies enabling adaptive threat detection, automated response, and predictive security analytics. This study examines the evolution of cybersecurity architectures designed to protect national digital infrastructures, focusing on the emergence of AI-assisted Security Operations Centers (SOCs), the integration of Security Information and Event Management (SIEM) platforms with Extended Detection and Response (XDR) systems, and the application of machine learning models for large-scale threat detection. The analysis also explores the relevance of these technologies in governmental and financial infrastructures, where the resilience of digital systems is closely associated with national security and economic stability. Evidence from recent studies indicates that AI-assisted cybersecurity frameworks can enhance detection accuracy, reduce operational workload in SOC environments, and support proactive defense strategies in complex digital ecosystems.